Ability Media Robotics (Robot Soccer) in Fostering the Learning Interest of Students in the Subjects of Physics - Indica Yona Okyranida; Dandan Luhur Saraswati; Neng Nenden Mulyaningsih (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2020)
In this research was quantitative research to know the increase of interest in student learning by using robotic media. Robotic media used in this study uses the robot soccer. The design of these studies using experimentation. Interest in student learning data taken using question form interest in learning. This dalampenelitian data processing using trial T or t-test were analyzed using SPSS. The results showed that there was an increased interest in learning of students in the subjects of physics using media Robotics (robot soccer) with the acquisition value of the pretest of 66.81 postest and value of 77.05.